Desafios das cidades inteligentes e a busca por soluções inteligentes - Oakes, Anne Richardson (Unisanta Law and Social Science, 2025)
Urban living is currently a reality for half of the world’s population. Projections suggest that by 2050, this figure will rise to approximately two thirds.  As this trend continues, cities that represent the major provider and regulator of the resources, infrastructure and services that support our lives, increasingly find technological solutions to navigate and support their governance and service provision.  This paper considers how the law and legal structures might need to adapt to take account of these trends. It considers two issues in particular. The first is the phenomenon of the ‘smart city’ initiative which harnesses the use of ICT within urban spaces to address economic, social and environmental challenges. The second is the issue of democracy and in particular those claims for citizen participation in urban policy and decision-making that are sometimes conceptualised in terms of human rights but were given an intellectual basis under the rubric of the Right to the City by the French urban theorist and public intellectual Henri Lefebre. The question then concerns the interaction between the two. As cities increasingly turn to smart technology what are the implications for their citizens in terms of a) smart technology surveillance with all that implies for interference with individual privacy and b) the ability of citizens to navigate and play an active role in the complex networks of legal frameworks and public and private partnerships which these initiatives require.